Ernst Haas - abstract - Campany, David 1967- (Prestel, 2024)
Three decades after its completion, Haas’ most personal and least-known project is now available for the first time in this exquisitely produced book. Presented in a clean and spare design, this volume features reproductions of superb quality that allow readers to appreciate his mastery of color, light, and composition, and his ability to capture the mystery of daily life. For this collection Haas drew on images made in all phases of his career from 1952 to 1984, and, despite the title, most of these photographs are not abstract but rather clear, focused, well-exposed images of recognizable surfaces from the observable world around him: crumbling paint, graphic road markings, fabric, liquids, detritus, decay, and torn posters. David Campany’s eloquent introductory essay lays the groundwork for a deep appreciation of the slideshow which, in book form, can be savored and understood in an entirely new way
Zusätzliches Online-Angebot unter QR-Code abrufbar (Video on Vimeo)
Keywords: Haas, Ernst -- 1921-1986; Geschichte 1952-1984; Fotografie; kunst; fotografie; magnum photos; usa; kodachrome; analog photography; Bildband